2015
DOI: 10.4238/2015.july.27.16
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of VEGF gene polymorphisms in the risk of osteosarcoma

Abstract: ABSTRACT. We conducted a case-control study in a Chinese population, and assessed whether the VEGF -634G/C, +936C/T, and +1612G/A polymorphisms could affect the risk of osteosarcoma and its association with environmental factors. A total of 180 consecutive osteosarcoma patients and 360 controls were included in our study. The genotypes of VEGF -634G/C, +936C/T, and +1612G/A were determined by the polymerase chain reaction-restriction fragment length polymorphism assay. Conditional logistic regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…Sensitivity analysis (Figure 3B for the dominant model) was conducted and the results were stable on the whole. Cumulative analysis (Figure 3C for dominant model) demonstrated a significant protective association from the study of Zhang et al in 2015 [32]. No publication bias was found in the funnel plot and Egger's test (C vs. G, P = 0.80; CC vs. GG, P = 0.55; GC+CC vs. GG, P = 0.61; CC vs. GG+GC, P = 0.19) (Figure 3D for the dominant model).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Sensitivity analysis (Figure 3B for the dominant model) was conducted and the results were stable on the whole. Cumulative analysis (Figure 3C for dominant model) demonstrated a significant protective association from the study of Zhang et al in 2015 [32]. No publication bias was found in the funnel plot and Egger's test (C vs. G, P = 0.80; CC vs. GG, P = 0.55; GC+CC vs. GG, P = 0.61; CC vs. GG+GC, P = 0.19) (Figure 3D for the dominant model).…”
Section: Resultsmentioning
confidence: 92%
“…For the +936C/T polymorphism, the seven studies included a total of 1,350 cases and 1,706 controls [27, 30–35]. For the +1612 G/A polymorphism, the six studies included a total of 1,166 cases and 1,524 controls [27, 30–32, 34, 35]. For the −634 G/C polymorphism, the six studies involved a total of 1,166 cases and 1,524 controls [27, 30–32, 34, 35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Zhang et al . ,b; Zhao et al . ) consisted of 1220 cases and 1576 controls met the inclusion criteria, and all of studies were conducted in Chinese Han population.…”
Section: Resultsmentioning
confidence: 99%
“…Not all people exposed to similar risk factors develop osteosarcoma, however, which suggests that hereditary factors may influence susceptibility. Several previous studies have reported that gene polymorphisms play an important role in osteosarcoma, including variations in VEGF, FGF2, GSTs, NFKB1, RECQL5 and CTLA-4 genes (He et al, 2014;Zhi et al, 2014;Han et al, 2015;Li et al, 2015;Zhang et al, 2015;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 98%